2011
DOI: 10.1165/rcmb.2010-0288oc
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Activation of the Innate Immune System to Prevent Respiratory Viral Infections

Abstract: Drugs that can rapidly inhibit respiratory infection from influenza or other respiratory pathogens are needed. One approach is to engage primary innate immune defenses against viral infection, such as activating the IFN pathway. In this study, we report that a small, cell-permeable compound called 5,6-di-methylxanthenone-4-acetic acid (DMXAA) can induce protection against vesicular stomatitis virus in vitro and H1N1 influenza A virus in vitro and in vivo through innate immune activation. Using the mouse C10 br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…In line with this observation, ectopic expression of the Thr 946 allele in K562 cells resulted in a relative decrease in IFNα, TNFα, and Casp8 expression and concomitant increase in MX1, MAVS, and MAPK8 [52]. As IFNβ is essential for expression of MX1, these results suggest an IFNβ-mediated IFN response [58,59]. Furthermore, these studies support the trend of reduced IFNα reported by Polychronakos et al [56].…”
Section: Rs1990760/a946t Effects On Mda5 Functionsupporting
confidence: 85%
“…In line with this observation, ectopic expression of the Thr 946 allele in K562 cells resulted in a relative decrease in IFNα, TNFα, and Casp8 expression and concomitant increase in MX1, MAVS, and MAPK8 [52]. As IFNβ is essential for expression of MX1, these results suggest an IFNβ-mediated IFN response [58,59]. Furthermore, these studies support the trend of reduced IFNα reported by Polychronakos et al [56].…”
Section: Rs1990760/a946t Effects On Mda5 Functionsupporting
confidence: 85%
“…Nonetheless, modulation of host pathways for enhancement of the innate immune response through chemicals could be a viable strategy for the development of antiviral therapy, and has been of growing interest recently [25,26]. It can be expected that such immunomodulators are effective against a range of different viral pathogens through the many facets of the host immune response.…”
Section: Iav Ibv Rsv Hrv Sars-and Mers-covmentioning
confidence: 99%
“…Despite showing promise in initial phase II trials for treatment of nonsmall cell lung cancer in combination with the current chemotherapeutic regimen of carboplatin and paclitaxel (8,9), DMXAA did not show efficacy in the most recent phase III clinical trial (10). However, induction of IFN-␤ also allows DMXAA to act as an antiviral agent during in vitro infection of multiple cell types with a variety of influenza strains (including a Tamiflu-resistant strain) and during in vivo infection of mice with mouse-adapted influenza A virus (11,12). Combined with its use as a tool to study signaling pathways activated by intracellular pathogens, understanding the mechanism of DMXAA-mediated up-regulation of IFN-␤ would benefit multiple fields of study.…”
Section: 6-dimethylxanthenone-4-acetic Acid (Dmxaa)mentioning
confidence: 99%